2013
DOI: 10.1017/s1041610213000628
|View full text |Cite
|
Sign up to set email alerts
|

Family caregiving at the intersection of private care by migrant home care workers and public care by nursing staff

Abstract: An indication of the lack of clarity concerning family caregiving roles stems from the finding that family members were frequently viewed as unengaged and neglectful, yet at times they were criticized for being overly involved in patient care. Implications for the care of hospitalized older adults are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…In five articles, caregivers view care management as their primary responsibility (Ayalon, Halevy‐Levin, Ben‐Yizhak, & Friedman, ; Kirk, ; Linderholm & Friedrichsen, ; Stephan, Möhler, Renom‐Guiteras, & Meyer, ; Toscan, Mairs, Hinton, & Stolee, ). In the study of Stephan et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In five articles, caregivers view care management as their primary responsibility (Ayalon, Halevy‐Levin, Ben‐Yizhak, & Friedman, ; Kirk, ; Linderholm & Friedrichsen, ; Stephan, Möhler, Renom‐Guiteras, & Meyer, ; Toscan, Mairs, Hinton, & Stolee, ). In the study of Stephan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses underlined the importance of family visits and upheld the same expectations for emotional care by caregivers: families can give emotional support when they come to see the care recipient. They don't have to do anything else (Ayalon et al., ). However, the same study showed different views on caregivers’ responsibilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations